Comments on “Progressive Muslims and Islamic Jurisprudence," by Kecia Ali - Saleem, Zainab (Islamic Studies, 2023)
This is a review of Kecia Ali’s book chapter “Progressive Muslims and Islamic Jurisprudence.” Ali argues for a need to reform Islamic family law, such that it is representative of the contemporary context. Her argument is based on her research on Islamic family law in Islamic jurisprudence manuals in which she found a significant influence of gender norms in the formative period of Islam (until the third century AH) in shaping its content. She concludes by highlighting that as the gender norms in the formative period influenced Islamic family law, we need to reform Islamic family law for it to reflect contemporary gender norms. This write-up explores Ali’s argument and methodology and situates her argument within other scholarship on rethinking Islamic family law. It concludes by providing an evaluation of Ali’s argument.